ANALISIS PENGARUH BEBAN KERJA TERHADAP KELELAHAN PEKERJA PADA DEPARTEMEN PAINTING MENGGUNAKAN METODE CVL DAN KONSUMSI ENERGI - Andryan Rizky Zahran; Nana Rahdiana; Sani Suhardiman (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2024)
Workload refers to worker activities that require strength and endurance and physical energy. Thecompany under study is a manufacturing company engaged in the automotive sector in the paintingdepartment of four-wheeled vehicle production in Karawang. A related challenge is the dominance ofmanual processes in some parts of the company. The purpose of the study is to understand theworkload on each shift and see the effect of worker fatigue by calculating the amount of energyconsumption and using the CVL approach. The research results from the morning shift found that theaverage %CVL percentage in various production sections was as follows: Mixing 29.08%, Top coat27.96%, Sanding ED 25.22% and Repair 25.11%. and for the night shift as follows: Mixing 30.12%,Top coat 29.65%, Sanding ED 25.92% and Repair 22.58%. It can be seen from the results of the studythat the average CVL (%) on each shift does not cause excessive fatigue in workers. Although ingeneral the phenomenon of fatigue does not occur, according to the calculations of some workers,especially at the mixing and topcoat stages, there is a higher percentage of %CVL with an averageCVL value of 30% and requires improvement. In addition, the results of energy consumptioncalculations show that all parts are classified as work that uses low to very low energy consumption.